Incidence and Characteristics of Cerebellar Atrophy/Volume Loss in Children with Confirmed Diagnosis of Tuberous Sclerosis Complex - Livja Mertiri; Eugen Boltshauser; Stephen F. Kralik; Nilesh K. Desai; Maarten H. Lequin; Thierry A. G. M. Huisman (MDPI AG, 2024)
Objectives: The goal of our study was to determine the incidence of cerebellar atrophy, assess the imaging findings in the posterior fossa and determine the incidence of hippocampal sclerosis in a cohort of pediatric patients with confirmed tuberous sclerosis complex (TSC). Material and methods: MRI studies of 98 TSC pediatric patients (mean age 7.67 years) were evaluated for cerebellar atrophy, cerebral/cerebellar tubers, white matter lesions, subependymal nodules, subependymal giant cell astrocytomas, ventriculomegaly, and hippocampal sclerosis. Clinical charts were revisited for clinical symptoms suggesting cerebellar involvement, for seizures and treatment for seizures, behavioral disorders and autism. Results: Cerebral tubers were present in 97/98 cases. In total, 97/98 had subependymal nodules, 15/98 had SEGA, 8/98 had ventriculomegaly and 4/98 had hippocampal sclerosis. Cerebellar tubers were found in 8/98 patients (8.2%), whereas cerebellar atrophy was described in 38/98 cases (38.8%). In 37/38 patients, cerebellar volume loss was mild and diffuse, and only one case presented with left hemi-atrophy. Briefly, 32/38 presented with seizures and were treated with anti-seizure drugs. In total, 8/38 (21%) presented with behavioral disorders, 10/38 had autism and 2/38 presented with seizures and behavioral disorders and autism. Conclusions: Several studies have demonstrated cerebellar involvement in patients with TSC. Cerebellar tubers differ in shape compared with cerebral tubers and are associated with cerebellar volume loss. Cerebellar atrophy may be focal and diffuse and one of the primary cerebellar manifestations of TSC, especially if a TSC2 mutation is present. Cerebellar degeneration may, however, also be secondary/acquired due to cellular damage resulting from seizure activity, the effects of anti-seizure drugs and anoxic-ischemic injury from severe seizure activity/status epilepticus. Further, prospective studies are required to identify and establish the pathogenic mechanism of cerebellar atrophy in patients with TSC.